Re-animating Ghosts: Materiality and memory in hauntological appropriation - Michael Peter Schofield (International Journal of Film and Media Arts, 2019)
This research examines the spectrality of animation and other media based on the photographic trace. Using diverse examples from popular culture and the author’s own investigative practice in media art, this paper looks at how archival media is re-used and can be brought back to life in new moving image works, in a gesture we might call hauntological appropriation.